2018
DOI: 10.3389/fneur.2018.00014
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Brain Intrinsic Networks and Executive Dysfunction in Cirrhotic Patients without Overt Hepatic Encephalopathy

Abstract: Objective: Patients with cirrhosis often exhibit cognitive deficits, particularly executive dysfunction, which is considered a predictor of overt hepatic encephalopathy (OHE). We examined brain intrinsic networks associated with executive function to investigate the neural basis of this cognitive deficiency in cirrhosis. Methods:Resting-state functional MRI data were acquired from 20 cirrhotic patients and 18 healthy controls. Seed-based correlation analysis was used to identify the three well-known networks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…Given that CIT1 and CIT2 involve auditory selective attention and that CIT3 involves auditory alternating attention, the cognitive threshold of patients with CLD might be auditory alternating attention (or cognitive flexibility). The current findings resembled previous findings where selective attention (Felipo et al, 2012 ) and cognitive flexibility (Yang et al, 2018 ) deteriorated in patients with liver-related diseases. The tasks employed in the previous studies are visual-oriented, so our findings revealed that the deterioration of selective attention and of cognitive flexibility exists similarly in an auditory modality.…”
Section: Discussionsupporting
confidence: 91%
“…Given that CIT1 and CIT2 involve auditory selective attention and that CIT3 involves auditory alternating attention, the cognitive threshold of patients with CLD might be auditory alternating attention (or cognitive flexibility). The current findings resembled previous findings where selective attention (Felipo et al, 2012 ) and cognitive flexibility (Yang et al, 2018 ) deteriorated in patients with liver-related diseases. The tasks employed in the previous studies are visual-oriented, so our findings revealed that the deterioration of selective attention and of cognitive flexibility exists similarly in an auditory modality.…”
Section: Discussionsupporting
confidence: 91%
“…Our approach builds on our previous work with intracranial EEG, where we show that patients generally have better seizure outcomes when high-strength nodes are surgically removed (27)(28)(29)(30). Other groups have reported similar findings from intracranial EEG (31)(32)(33)(34)(35)(36)(37). With MEG data, Nissen et al (9) showed in a cohort of 22 patients, that interictal source localized network hubs overlapped with the resection in seizure-free patients only.…”
Section: Discussionsupporting
confidence: 53%
“…MHE patients had fewer hubs than those in the HC group (15 vs. 17) and showed a different distribution of network hubs from the HC group. They lost hub nodes mainly from the bilateral frontal lobe, right parietal lobe, as well as the left insular cortex, which are areas that are most frequently affected in MHE (Hsu et al, 2012 ; Zhang et al, 2012 ; Chen et al, 2013 ; Yang et al, 2018 ). Thus, our finding further indicated the selective vulnerability of these areas in the case of MHE.…”
Section: Discussionmentioning
confidence: 99%